Assessing the Relevance of the 1992 Namibian Language in Education Policy (NLiEP) Document - Iipinge, Kristof; Banda, Felix; Norro, Soili (Informa UK Limited, 2025)
The current Namibian Language in Education Policy (NLiEP) document was first introduced in 1991 immediately after the country gained its independence. Even though this document has been in existence for more than 30 years, it has never been formally assessed or modified despite the changing socio-economic and language practices. Using four criteria (authenticity, representativeness, meaning, and credibility) suggested to evaluate documents for relevance, the article seeks to establish the relevance of the current NLiEP document. The findings suggest that the NLiEP document is out of touch with the developing multilingual realities of Namibians and the current debates on multilingual pedagogies in postcolonial Africa and the Global South generally. The article concludes with a discussion of an ideal prospective language policy document for Namibian schools.